Effects of Site-Directed Mutagenesis of Cysteine on the Structure of Sip Proteins - Wang, Lin; Ding, Ming-Yue; Wang, Jing; Gao, Ji-Guo; Liu, Rong-Mei; Li, Hai-Tao (Frontiers in Microbiology, 2022)
Bacillus thuringiensis, a gram-positive bacteria, includes three insecticidal proteins, Vip (vegetative insecticidal protein), Cry (Crystal), and Sip (Society for Invertebrate Pathology). Among them, Sip showed good insecticidal activity against coleopterans, however, data on Sip1Aa protein remain limited due to severe Sip protein inclusion, which highlights the importance of further studies on Sip1Aa protein. Therefore, this study aimed to obtain purified Sip proteins that are free of other bands by continuously changing the separation and purification conditions of the mutant proteins. Sip1Aa has a strong toxic effect on the members of order Coleoptera. Disulphide bonds play an important role in the stability and function of the proteins. Therefore, herein, we successfully constructed mutant proteins with high insecticidal activity. The tertiary structure of Sip1Aa protein was analysed using homologous modelling and other bioinformatics methods to predict the conserved domain of Sip1Aa protein. A cysteine was used to replace these amino acids via site-directed mutagenesis. We successfully constructed Sip149-251, Sip153-248, Sip158-243, and Sip178-314 mutant proteins, with higher solubility compared to Sip1Aa. The mutant proteins Sip153-248 and Sip158-243 were the most stable compared to Sip1Aa, followed by Sip149-251 and Sip178-314. The insecticidal activity of Sip153-248 was 2.76 times higher than that of Sip1Aa, and that of Sip158-243 was 2.26 times higher than that of Sip1Aa. The insecticidal activities of Sip149 – 251 and Sip153 – 248 did not change significantly compared with Sip1Aa. Meanwhile, the basic structural properties, physicochemical properties, and mutation-site spatial structure of Sip1Aa and mutant proteins were analysed. These results would provide the molecular basis for the application of Sip1Aa in coleopteran insect control and would contribute to the study of Sip1Aa insecticidal mechanism as well.